»Så de lod mig bare være …« – eksempler på veje fra psykiatrisk til retspsykiatrisk patient - Møllerhøj, Jette; Brandt-Christensen, Mette; Stølan, Liv Os (Nordisk Tidsskrift for Kriminalvidenskab, 2020)
Abstract The aim of this study is to provide various perspectives on two examples in which long term psychiatric patients committed serious crimes and consequently became mentally disordered offenders. The two patients involved were found guilty, but were not punishable under Danish law and were instead sentenced to placement in a psychiatric facility. When looking at these cases from the perspective of various stakeholders, e.g., relatives, health care professionals, the patients themselves, a number of potential risk and protective factors come to light. The analysis is followed by a discussion of whether similar situations can be prevented and, if so, how. We recommend an intensified focus on risk and protective factors, as well as preventive measures, and an increased cooperation and knowledge sharing between patients, relatives, networks, hospital psychiatry and psychosocial rehabilitation units provided within municipalities.